"Do Whatever you Can to Try to Support that Kid": School Counselors' Experiences Addressing Student Homelessness. (2017) - Havlik, Stacey A.; Rowley, Patrick; Puckett, Jessica; Wilson, George; Neason, Erin
This qualitative study explored the experiences of 23 school counselors in addressing the needs of students experiencing homelessness. Phenomenological analysis revealed two overarching themes: (a) school counselors as the first line of support and (b) the desire to help while feeling helpless. Findings suggest that participants feel underprepared to support the needs of students experiencing homelessness. They face challenges identifying students and addressing their needs and rely on collaborations with other professionals.